OP05 Association between lifetime occupational physical activities and grip strength at retirement age: findings from the hertfordshire cohort study. (31st August 2015) - D'Angelo, S; Syddall, H; Coggon, D; Palmer, KT; Cooper, C; Sayer, A Aihie; Walker-Bone, K
Abstract : Background: Sarcopenia, the loss of skeletal muscle mass and function with age, is common among older people. Grip strength is a frequently-used, simple, reproducible clinical measure of muscle strength, and a marker of sarcopenia, which has been shown to be an independent predictor of disability and mortality in later life. Given its prognostic importance, it is crucial to understand its determinants. There is some evidence that leisure time physical activity is a positive determinant of grip strength, but little is known about the role of physical occupational activity. We aimed to investigate the role of lifetime occupational physical activity on grip strength measured at retirement age. Methods: Data come from the Hertfordshire Cohort Study where information on lifetime exposure to three heavy physical workload measures (standing/walking ≥4 h/day; lifting ≥25 kg; and work sufficiently physical to induce sweating) was collected. Grip strength was measured three times on each hand and then the maximum value was used. Multivariable linear regression was used to investigate the cross-sectional associations between occupational activities and grip strength, controlling for age, body size measurements, social class, smoking, diet, and age upon leaving full time education. Results: Analysis was restricted to 1, 419 men with complete data who had worked at least 20 years. Among men who reported medium exposure to heavy lifting in their occupation, grip strength was significantly reduced compared with men reporting low levels of exposure, and this association persisted after full adjustment for confounders (β = –1.22; 95% CI = –2.21 to –0.24). Men who reported standing/walking ≥4 h/day for at least 36 years of working life (medium/high exposure), had significantly worse grip strength than men reporting low levels of this exposure, but after adjustment for potential confounders these associations were lost. Similarly, working at physical intensity enough to induce sweating was not significantly associated after adjustment for confounders. Conclusion: Heavy occupational activities are negatively associated with grip strength at retirement age. We hypothesise that any potential beneficial effect of intensive physical work is offset by the negative impact of other socio-economic factors (diet/lifestyle/deprivation/education) that determine career opportunities.